2018
DOI: 10.1002/ajpa.23424
|View full text |Cite
|
Sign up to set email alerts
|

The WITS Atlas: A Black Southern African dental atlas for permanent tooth formation and emergence

Abstract: Similarities in advancement in tooth formation and emergence across sub-Saharan Africa suggest that the WITS Atlas can be used for those populations as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…LEH in the sample were mainly found on the canines, which form between six months and six years of age, indicating metabolic stress occurring during these ages (Goodman & Rose, ; Esan & Schepartz, ). This is consistent with the age of weaning that is known to occur among Khoesan between the ages of two and four (Clayton, Sealy, & Pfeiffer, ; Konner & Worthman, ); a period described as often traumatic, which can lead to caloric deficiency, impact development and increase susceptibility to infection or illness (Konner, ; Lee & DeVore, ; Stinson, ; Truswell & Hansen, ).…”
Section: Health and Stressmentioning
confidence: 99%
“…LEH in the sample were mainly found on the canines, which form between six months and six years of age, indicating metabolic stress occurring during these ages (Goodman & Rose, ; Esan & Schepartz, ). This is consistent with the age of weaning that is known to occur among Khoesan between the ages of two and four (Clayton, Sealy, & Pfeiffer, ; Konner & Worthman, ); a period described as often traumatic, which can lead to caloric deficiency, impact development and increase susceptibility to infection or illness (Konner, ; Lee & DeVore, ; Stinson, ; Truswell & Hansen, ).…”
Section: Health and Stressmentioning
confidence: 99%
“…26,27 Due to the secular trends of growth resulting from changing diet and other environmental factors, there is need for current data on eruption patterns in Kenya In addition; ethnicity has been found to play a role in the development of third molars. [28][29][30][31] Interpretation of dental age through observation of eruption patterns should be done cautiously following a thorough dental examination since local or exogenous factors such as tooth crowding, early extraction, dental impaction and nutritional status have been found to either delay or hasten tooth eruption. 32 Therefore, a reasonable margin of error should also be provided.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is paucity of literature regarding the applicability of the London Atlas to other population groups, e.g., Sub-Saharan Africa. In 2018, Esan and Schepartz [ 13 ] compared the London Atlas with the WITS Atlas, which the aforementioned authors created using the Demirjian method for the SA Black population of Gauteng province in South Africa. Unfortunately, the comparison revealed that the London Atlas was not suitable for age estimation in this population group [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Esan and Schepartz [ 13 ] compared the London Atlas with the WITS Atlas, which the aforementioned authors created using the Demirjian method for the SA Black population of Gauteng province in South Africa. Unfortunately, the comparison revealed that the London Atlas was not suitable for age estimation in this population group [ 13 ]. The study by Esan and Schepartz [ 13 ] compared the developmental stages of the London Atlas to the WITS Atlas; however, they did not directly investigate the applicability of the London Atlas to the South African (SA) population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation